Anamnestic risk factor evaluation of patients carrying carbapenem-resistant Enterobacterales and/or Acinetobacter baumannii - impact on infection control management at a German University Hospital - Hofmann, Franziska; Heudorf, Ursel; Steul, Katrin; Wichelhaus, Thomas A; Besier, Silke; Hogardt, Michael; Hack, Daniel; Steinmann, Elvira; Kempf, Volkhard A J; Reinheimer, Claudia (German Medical Science GMS Publishing House, 2020)
Background: Carbapenem-resistant and are of major concern in terms of infection prevention and control. This study evaluated factors that may increase the frequency of and with carbapenem resistance (CR) in patients admitted to a German University Hospital for implementation of optimized infection control management.Methods: A five-year-retrospective epidemiological cohort analysis was conducted on anamnestic risk factors for carrying and/or with CR in patients who were first tested positive for these species at University Hospital Frankfurt (UHF) between January 2013 and June 2018. Results: 364 patients were tested positive for and/or with CR, resulting in n=400 bacterial isolates in total, with being the most frequently detected species (n=146/400; 36.5%; 95% confidence interval: 31.8-41.4). In patients who were tested positive for and/or with CR, any hospital stay within the previous 12 months was the most frequently reported common factor (n=275/364; 75.5%; 70.8-79.9).Conclusion: A hospital stay within the previous 12 months, including hospitals in Germany and abroad, is a frequent characteristic of patients who tested positive for and/or with CR. Upon admission, any previous hospital stay of the given patient within the previous 12 months should be determined. Infection control strategies such as screening measures need to be adapted to these patient groups in hospital settings. In order to reflect the varying determinants in "nosocomial" cases in greater detail, the existing criteria used to characterize "nosocomial detection" of gram-negative bacteria with CR should be reviewed.